Continuous changes in leg stiffness using a mass-spring-damper model with an actuator during the step phase of the triple jump - Yamamoto, J.; Miyazaki, T.; Koike, S.; Fujii, N. (ISBS Proceedings Archive (Michigan), 2021)
The purpose of this study was to examine a calculation method of the leg stiffness using the simplified leg model for evaluating the continuous changes in leg stiffness during the step phase of the triple jump. The leg stiffness is the ratio of the ground reaction forces to a displacement of the simplified leg length. We compared the difference in the leg stiffness between the previous method and the proposed method in this study. There was a non-linear and exponential relationship between the displacement of the simplified leg length and the elastic force. The peak value of leg stiffness calculated by the previous method was larger than that by the mass-spring-damper model with an actuator of the proposed method in this study. The previous method could overestimate the leg stiffness during the triple jump. The leg stiffness of the proposed method has a potential for representing the muscle-tendon behaviors during the triple jump.